2015
DOI: 10.1007/s00707-015-1427-y
|View full text |Cite
|
Sign up to set email alerts
|

On effective properties of materials at the nano- and microscales considering surface effects

Abstract: In the last years, the rapid increase in the technical capability to control and design materials at the nanoscale has pushed toward an intensive exploitation of new possibilities concerning optical, chemical, thermoelectrical and electronic applications. As a result, new materials have been developed to obtain specific physical properties and performances. In this general picture, it was natural that the attention toward mechanical characterization of the new structures was left, in a sense, behind. Anyway, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(61 citation statements)
references
References 112 publications
0
60
0
1
Order By: Relevance
“…This expression is substituted into equilibrium Equations (8). The resulting equations are solved with respect to u n,m using DFT.…”
Section: Displacement Field In a Triangular Lattice With Doubly Periomentioning
confidence: 99%
See 1 more Smart Citation
“…This expression is substituted into equilibrium Equations (8). The resulting equations are solved with respect to u n,m using DFT.…”
Section: Displacement Field In a Triangular Lattice With Doubly Periomentioning
confidence: 99%
“…Although the continuum mechanics modelling is expected to be appropriate for the effective properties [4], it may become inadequate at microscale, in particular, near vacancies, where the discreteness plays important role [5,6]. For example, Krivtsov and Morozov [7] have shown that the effect of discreteness is significant even in the absence of surface tension [8]. Examination of these issues is the main motivation for the present work.…”
Section: Introductionmentioning
confidence: 97%
“…A more complex form of (4) is discussed in [13]. For infinitesimal deformations of an isotropic material, the surface strain energy density is given by the formulas [39,40] …”
Section: Basic Equations Of Surface Elasticitymentioning
confidence: 99%
“…Dell'Isola et al [4] reported on the status of modeling and analyses of materials exhibiting a rich and varied macroscopic response conferred by complex microstructures. Eremeyev discussed new methods and techniques for modeling the behavior of nanostructured materials considering surface properties to determine their actual material properties at the macroscale using the Gurtin-Murdoch model of surface elasticity [37]. Dell'Isola et al [38] considered a discrete spring model for extensible beams and proposed a heuristic homogenization technique to formulate a continuum fully nonlinear beam model.…”
Section: Introductionmentioning
confidence: 99%